Students Perception on the Use of Speech Texter Application in Teaching Pronunciation Skills - Maspufah Maspufah (Universitas Pahlawan Tuanku Tambusai, 2021)
Teaching pronunciation for EFL, students ideally need to learn how to produce sound like a native speaker. Students should be assisted to practice and drill the correct pronunciation. However, teaching pronunciation in pandemic covid-19 situation became problematic not only for the lecturers but also for students. This research aimed to find out the students’ perception on the use of speech texter application in teaching pronunciation skill. The method of the research was descriptive qualitative. The subject of the research was the first semester students of 2020/2021 academic year which consist of 18 students. The instrument used to collect the data was in the form of semi-structured interview. There were 4 semi-structured interview gave to the students. The data were analyzed by using threeanalysiscomponents: datareduction,datadisplay,and conclusiondrawing. After analyzing the data, the result showed that the use of speech texter application was interesting and motivated them to drill the pronunciation until they produced the correct words. Then, they were also sure to be able to speak with the correct pronunciation after using the application. Thus, it can be concluded that students have a positive perception on the use of speech texter application in teaching pronunciation skill.